POST-TRAUMATIC STRESS DISORDER IN THE STATIONERY SHOP NOVEL BY MARJAN KAMALI - Yoana Ardesis (fsip.teknokrat.ac.id, 2022)
In this thesis entitled Post-Traumatic Stress Disorder in The Stationery Shop Novel by Marjan Kamali, the writer describes post-traumatic stress disorder. PTSD (Post Traumatic Stress Disorder) is a mental health condition triggered by a traumatic event. The purpose of this study is to identify the post-traumatic stress disorder raised by Roya. To enhance the examination of post-traumatic stress disorder, the writer utilizes the theory of Gerald C. Davison (2006) to analyze the symptoms, causes, and effects of post-traumatic stress disorder. In addition, the American Psychiatric Association's (APA) theory in its publication Diagnostic and Statistical Manual of Mental Illness: DSM-5 was applied in this research study for more information and as a supporting theory on the symptoms of Post- Traumatic Disorder. In this study, the writer used qualitative research techniques to describe post-traumatic stress disorder. This study can enhance the reader's understanding of a person's psychological state and mental disorder in response to a traumatic event or circumstance.